1983
DOI: 10.1007/bf00276256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interpretation and analysis of diallel crosses with animals

Abstract: A genetic framework was developed for the interpretation of statistical parameters estimated from a diallel experiment among a fixed set of lines. These included average direct genetic, average maternal genetic, general combining ability, reciprocal, and line and specific direct and maternal heterotic effects. The genetic model is based on direct and maternal additive and dominance genetic effects as would be expected in animal species. The model assumes that dominance is the underlying basis of heterosis. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 19 publications
1
85
0
2
Order By: Relevance
“…In genetic terms, the SCA represents the non-additive effect of putting gametes together in pairs to make the F1 genotypes. Eisen et al (1983) concluded that the highest absolute values of SCA of a cross combination occur when gene frequency of both lines diverge the most from mean gene frequency at loci exhibiting favourable dominance direct effects. Extending the concept of SCA at the level of gene expression, Kiekens et al (2006) concluded that the SCA represents the interaction of the gametes i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In genetic terms, the SCA represents the non-additive effect of putting gametes together in pairs to make the F1 genotypes. Eisen et al (1983) concluded that the highest absolute values of SCA of a cross combination occur when gene frequency of both lines diverge the most from mean gene frequency at loci exhibiting favourable dominance direct effects. Extending the concept of SCA at the level of gene expression, Kiekens et al (2006) concluded that the SCA represents the interaction of the gametes i.e.…”
Section: Resultsmentioning
confidence: 99%
“…= the k-th observation on the progeny of a mating of a dam from the j-th line with a sire of the i-th line in the h-th type of breeding (purebred or crossbred, h = 1,2), = mean of the purebred and crossbreds, = effects common to all progeny of the hth type of breeding (purebred or crossbreds); similar to average heterosis ( ) in model A (Eisen et al, 1983), = effect common to all progeny of a mating between a dam of the i-th line and a sire of the i-th line;…”
Section: Wherementioning
confidence: 99%
“…The least squares estimators of the parameters are as shown in (Jakubec et al, 1987), where model A is the model developed by (Eisen et al, 1983) while model B is developed by (Harvey, 1960) and extended by (Jakubec et al, 1987). The choice of this model (Model B) is because it is the most appropriate when the parental lines are less than 4.…”
Section: Wherementioning
confidence: 99%
“…The mean of a cross or of a purebred strain was set up according to Gardner and Eberhart (1966), Wearden et al (1967) and Eisen et al (1983): …”
Section: Statistical Analysesmentioning
confidence: 99%